Effects of core position uncertainty on optical shape sensor accuracy. (June 2019) - Floris, Ignazio; Calderón, Pedro A.; Sales, Salvador; Adam, Jose M.
Graphical abstract: Highlights: Optical shape sensors consist of multiple single-core optical fibers. Core position errors are due to errors in the manufacturing process. In MCF, errors are in the range between a few hundred nanometers to one micrometer. The effects of core position errors on the precision of shape sensors are analysed. Abstract: Optical fiber sensors are now widely recognized as extremely reliable instruments to sense strain. Optical shape sensors consist of multiple single-core optical fibers or multicore optical fibers capable of sensing bending direction and curvature by comparing the longitudinal strain of different cores in an instrumented section and reconstructing the sensor shape. This paper describes a study on the effects of core position errors on the precision of optical shape sensors when measuring strain, bending direction and curvature, and identifies the role of measured curvature and core spacing (distance between section center and external cores), considering 7, 4, and 3-core fiber geometries, three of those most widely employed for sensing applications. The Monte Carlo technique was utilized to reproduce the measurement process. Forty-five simulations, including 3·10 6 trials, were carried out for each geometry with the aim of investigating the law of uncertainty propagation. The results of the analysis, applicable to both multiple single-core fibers and multicore optical sensors equipped with distributed or quasi-distributed strain-sensors, show the effects of core position uncertainty and will be useful for new sensor designs and user options by predicting the achievable performance of these devices.